2019
DOI: 10.46743/2160-3715/2019.3742
|View full text |Cite
|
Sign up to set email alerts
|

The Coach’s Journal: Experiences of Black Female Assistant Coaches in NCAA Division I Women’s Basketball

Abstract: In NCAA Division I women’s basketball, Black female coaches make up only a small percentage of the total number of coaches (i.e., 26%; NCAA, 2016) even though the majority of student-athletes are Black (i.e., 51%). Although these discrepancies have recently been recognized in sport studies literature (Borland & Bruening, 2010; LaVoi & Dutove, 2012), sport psychology researchers have yet to explore the underlying structural and psychological issues that lead to the underrepresentation of Black female co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Coping strategies identified in seven studies primarily facilitated women to become and remain as leaders in sport and were largely focused on managing gendered racism. Strategies included the use of humour, downplaying the severity of discrimination, lowering expectations, dressing and acting professionally, relying on social supports and prayer (Larsen et al, 2019; McDowell & Carter-Francique, 2017; Welch et al, 2021). Professional development (e.g., seminars and workshops) supported women from culturally diverse backgrounds to independently explore strategies to improve their competence and prevent pigeonholing for certain roles (Larsen et al, 2019; Rankin-Wright et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Coping strategies identified in seven studies primarily facilitated women to become and remain as leaders in sport and were largely focused on managing gendered racism. Strategies included the use of humour, downplaying the severity of discrimination, lowering expectations, dressing and acting professionally, relying on social supports and prayer (Larsen et al, 2019; McDowell & Carter-Francique, 2017; Welch et al, 2021). Professional development (e.g., seminars and workshops) supported women from culturally diverse backgrounds to independently explore strategies to improve their competence and prevent pigeonholing for certain roles (Larsen et al, 2019; Rankin-Wright et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, all four BIPOC women in the present study—three of whom also identified as lesbians—reported experiencing pushback. Prior research has shown that prejudice and discrimination toward LGBTQIA+ and BIPOC coaches exist (Carter-Francique, 2020; Krane & Barber, 2005; Larsen et al, 2019; Scheadler et al, 2021). Previous research also has acknowledged that BIPOC women in sport are subjected to both racism and sexism (Cooky et al, 2010; Litchfield et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By doing so, however, these leaders ignore critical problems and allow racial injustice to persist. Furthermore, there even is evidence of prejudice and discrimination toward LGBTQIA+ (Krane & Barber, 2005; Scheadler et al, 2021) and BIPOC college coaches (Carter-Francique, 2020; Larsen et al, 2019). Thus, some college coaches may consider engaging in advocacy to support their student athletes or the broader student population, university, and community and to challenge the complicit nature of many sport leaders.…”
Section: College Coaches and Engagement In Advocacymentioning
confidence: 99%
“…35 This analogy suggests that the higher the women climb, the more constricted the pathway and opportunities become, and only a few women manage to reach the top of their profession 35(p.455) This narrow road causes women coaches to experience marginalization and lack of control of their coaching progression, especially when aiming to high-performance contexts. 34,[36][37][38] In response to the need of advancing in the study of women's coaching careers, LaVoi and Boucher developed the Stages of Career Progression Model (SCPM) as an evolution of the original EIM, 27 which considers different stages in women's coaching careers. The stages are as follows: (a) entice, characterized by encouraging, convincing, and enticing women into sports coaching; (b) entry, referring to the initial movement into a coaching position; (c) engagement, containing aspects related to the participation of women with, and in, their workplace and colleagues; (d) exit, related to voluntarily or involuntarily leaving a coaching position and (e) energize, where resilience is fostered and the focus is on renewal and personal growth.…”
mentioning
confidence: 99%
“…35 This analogy suggests that the higher the women climb, the more constricted the pathway and opportunities become, and only a few women manage to reach the top of their profession 35 (p.455) This narrow road causes women coaches to experience marginalization and lack of control of their coaching progression, especially when aiming to high-performance contexts. 34,3638…”
mentioning
confidence: 99%